2016
DOI: 10.1149/2.0071609jes
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Charge Contribution from Thermally Treated Ni Foam as Current Collectors for Li-Ion Batteries

Abstract: In this report we have investigated the use of Ni foam substrates as anode current collectors for Li-ion batteries. As the majority of reports in the literature focus on hydrothermal formation of materials on Ni foam followed by a high temperature anneal/oxidation step, we probed the fundamental electrochemical responses of as received Ni foam substrates and those subjected to heating at 100 • C, 300 • C and 450 • C. Through cyclic voltammetry and galvanostatic testing, it is shown that the as received and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This finding was also well matched with the discovery of O'Dwyer, who also confirmed the increase in the H2O content in DMSO-based electrolyte. [178] In a sharp contrast, the (Figure 20b and 20c). [179] Excellent water stability was achieved by incorporating the ILs into the tricontinuous cathode passages where electron, ions, and oxygen flow.…”
Section: Ionic Liquid Electrolytementioning
confidence: 94%
“…This finding was also well matched with the discovery of O'Dwyer, who also confirmed the increase in the H2O content in DMSO-based electrolyte. [178] In a sharp contrast, the (Figure 20b and 20c). [179] Excellent water stability was achieved by incorporating the ILs into the tricontinuous cathode passages where electron, ions, and oxygen flow.…”
Section: Ionic Liquid Electrolytementioning
confidence: 94%
“…versus a Li counter/reference electrode). 10,11,18,33,38,39 While these approaches allow attainable specific capacities and fundamental lithiation mechanisms to be examined, the excess Li source afforded by the bulk Li counter electrode does not truly reflect the finite source of Li ions associated with typical cathodes used in conventional FCs. 40,41 Within FCs, the balancing of cathode (positive) and anode (negative) capacities (P:N ratio) is of critical importance for practical applications as any excess cathode requirement is heavily penalized from a weight perspective, potentially leading to a negation of the weight saving benefit of the advanced anode.…”
Section: Introductionmentioning
confidence: 99%
“…This often leaves areas of porous metal that are subject to oxidation, and these oxides can in some cases contribute significantly to the overall electrochemical response [47]. A case in point is work by Geaney et al who showed [48] how NiO formation on a nickel foam can eventually dominates the response of a Li-ion electrode when the areal mass coverage is low enough to expose oxidized Ni at the porous metal current collector surface. Figure 2 summarises some of the salient properties or architected or 3D printed metal lattices useful for EES, and by comparison to metal foams (Fig 2b) and solid state synthesis routes, rational design of structure, order and reproducibility is improved.…”
Section: Some Properties Of Porous Metallic Structures In Eesmentioning
confidence: 99%